2016
DOI: 10.2119/molmed.2015.00233
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Ventilation Augments Poly(I:C)-Induced Lung Injury via a WISP1-Integrin β3-Dependent Pathway in Mice

Abstract: Mechanical ventilation can improve hypoxemia, but can also cause the so-called ventilator-induced lung injury (VILI). Polyinosinic:polycytidylic acid (poly(I:C)), an analogue of natural double-strand RNA virus, can induce lung inflammation. The purpose of this study was to determine whether moderate tidal volume mechanical ventilation (MTV) augments poly(I:C)-induced lung injury, and if so, the mechanism responsible for it. Two μg/g poly(I:C) were instilled intratracheally in C57BL/6J wide type (WT) mice. They… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 28 publications
6
24
1
Order By: Relevance
“…In addition, we also found that pure over-distension on healthy mice lung could only raise WISP1 level, while it could not upregulate cytokine levels (the results were not shown in this paper). Reports about WISP1 mainly concentrated on WISP1/β-catenin signaling pathway [30], like our previous study about WISP1 interacting with β6 [19,31] or with β3 [32,33], which was related to alveolarcapillary permeability in VILI or ALI/ARDS.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, we also found that pure over-distension on healthy mice lung could only raise WISP1 level, while it could not upregulate cytokine levels (the results were not shown in this paper). Reports about WISP1 mainly concentrated on WISP1/β-catenin signaling pathway [30], like our previous study about WISP1 interacting with β6 [19,31] or with β3 [32,33], which was related to alveolarcapillary permeability in VILI or ALI/ARDS.…”
Section: Discussionsupporting
confidence: 56%
“…In-vitro mechanical stretch of type II epithelial cells activated innate immunity and increased WISP1 expression, providing fundamental support for its involvement in VILI [ 41 ]. We noted that intrapulmonary WISP1 is elevated in VILI [ 21 ], CLP [ 22 , 23 ], combined poly(I:C) and mechanical ventilation [ 42 ], and in the current report in combined CLP and MTV; neutralizing antibodies to WISP1 partially reduced lung injury and inflammation in all of these conditions. The potential convergence of WNT/β-catenin signaling and WISP1 adds to its importance in VILI [ 43 ] as well as WNT-mediated lung epithelial cell repair [ 44 ].…”
Section: Discussionmentioning
confidence: 58%
“…Although we 10 reported that WISP1-β6 complexes in lung were important in cecal ligation and puncture (CLP), the non-specificity of inhibition of integrins with RGD and the partial effect observed with neutralizing antibodies to β6 suggest that other RGD sensitive integrins may play a role. Less is known about β3 and WISP1, we recently found that WISP1-integrinβ3 interaction contributed to mechanical ventilation augmented PolyI:C induced lung injury 14 . αvβ3 integrin (vitronectin receptor, CD51/CD61) is a ubiquitous receptor that is expressed on a wide variety of cell types including differentiated macrophage 15 16 .…”
mentioning
confidence: 95%